Efektivitas Pelaksanaan Perda Pengelolaan Zakat di Kota Mojokerto dan Kabupaten Sidoarjo - Saf, Mhd. Abduh (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: Currently, local regulations on zakat (Islamic obligatory charity) management has been set up in many regions in Indonesia. InMojokerto and Sidoarjo regency, such local regulations are expected to be effective for improving the welfare of the society.This local zakat management that has the role to collect and distribute zakat is called BAZ (BadanAmil Zakat). It seems that the zakat management in Mojokerto and Sidoarjo is more effective under the present of such a local regulation. It can be seen from the increase number of the charity payers, the increase of BAZâs charity programs, and the operation costs charged to APBD (Regional Government Budget).If it is analyzed by the effectiveness legal theory, it can be concluded that the observance of a rule of law (the perda or local regulation on the charity management) in Mojokerto and Sidoarjo regency is a kind of the internalizational obedience. It is because such observance of a rule of law is in accordance with the intrinsic values adopted. In addition, such local regulations are obeyed because giving charity is one of the fundamental Islamic teachings. The values embodied in charity in Islam have a very clear purpose, benefit, and punishment in the world and in the hereafter. These Islamic values contribute dearly to the success of the application of this local regulation on the charity management.Keywords: Charity management, local regulation, effectiveness, and BAZ.Â Abstrak: Saat ini zakat telah diatur dalam bentuk suatu Peraturan Daerah seperti Peraturan Daerah tentang Pengelolaan Zakat di Kota Mojokerto dan Kabupaten Sidoarjo. Dengan adanya Perda tersebut, diharapkan efektif untuk meningkatkan kesejahteraan masyarakat khususnya di Kota Mojokerto dan Kabupaten Sidoarjo. Perkembangan pengelolaan zakat pada BAZ di Kota Mojokerto dan Kabupaten Sidoarjo dengan adanya Perda tentang pengelolaan zakat menjadi lebih efektif. Hal itu bisa dilihat dari bertambahnya jumlah mudhakki, peningkatan perolehan dana zakat serta biaya operasional BAZ yang dibebankan kepada APBD. Apabila dianalisis dengan teori efektivitas hukum, maka bisa diambil kesimpulan bahwa ketaatan terhadap suatu aturan hukum (dalam hal ini adalah Perda tentang Pengelolaan zakat) di Kota Mojokerto dan Kabupaten Sidoarjo bersifat ketaatan internalization, yakni suatu peraturan ditaati karena merasa aturan itu sesuai dengan nilai-nilai intrinsik yang dianut. Perda tentang pengelolaan zakat ditaati karena menunaikan zakat merupakan ajaran Islam. Nilai-nilai yang terkandung dalam ajaran Islam mengenai zakat sangat jelas baik tujuan, manfaat serta sanksi baik di dunia maupun di akhirat. Nilai-nilai inilah yang menjadi dasar dalam menaati Perda tentang Pengelolaan Zakat yang sesuai dengan ajaran Islam.Kata Kunci: Pengelolaan zakat, Perda, efektivitas dan BAZ